Review and data evaluation for high-temperature reduction of iron oxide particles in suspension. (8th August 2020) - Chen, Zhiyuan; Zeilstra, Christiaan; van der Stel, Jan; Sietsma, Jilt; Yang, Yongxiang
ABSTRACT: High-temperature reduction processes of iron oxide particles suspension are promising in carbon emission abatement. Recently, researchers have contributed abundant knowledge of the reaction mechanism and kinetics of iron oxide particles above 1473 K, while there was very limited information 10 years ago. Although the understanding of the high-temperature reduction of iron oxide particles is still not comprehensive, a brief review of the academic reports is helpful for the future work on this topic. The high-temperature reduction of iron oxide suspension is characterized by having: rapid reaction, obvious thermal decomposition and melting process. Evaluation of the kinetic data shows that the reduction process of single particles is not rate-determined by the diffusion process at the studied temperatures. The reaction rate constant is within 10 −2 –10 s −1 in these studies. Furthermore, comparing previous studies in iron oxide reduction field, the phase transformation and effect of gangue minerals to the reduction of iron oxide particles above 1473 K requires more input and research.